2018
DOI: 10.1002/ppul.24201
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of within‐breath impulse oscillometry parameters in children with asthma

Abstract: Background: Impulse oscillometry (IOS) measures respiratory resistance and reactance during tidal breaths and is a convenient tool for evaluation of lung function. Respiratory resistance and reactance can be measured separately during inspiration and expiration (inspiratory-expiratory analysis).Objective: We investigated the differences in inspiratory-expiratory measurements obtained using IOS between children with and without asthma. Methods:We analyzed 819 subjects aged 4-18 years, including asthmatic childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…Destes, (9) (69%) acrescentaram exames complementares sendo a espirometria o exame mais frequente. (1)(2)(3)(4)6,10,13,14,18) Quanto aos desfechos clínicos, cinco artigos (28%) abordaram alterações brônquicas, cinco (28%) investigaram possíveis discrepâncias entre a sensibilidade das medidas em diferentes equipamentos, bem como sua associação no estabelecimento do diagnóstico e, oito (44%) realizaram avaliações referentes a impedância pulmonar.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Destes, (9) (69%) acrescentaram exames complementares sendo a espirometria o exame mais frequente. (1)(2)(3)(4)6,10,13,14,18) Quanto aos desfechos clínicos, cinco artigos (28%) abordaram alterações brônquicas, cinco (28%) investigaram possíveis discrepâncias entre a sensibilidade das medidas em diferentes equipamentos, bem como sua associação no estabelecimento do diagnóstico e, oito (44%) realizaram avaliações referentes a impedância pulmonar.…”
Section: Resultsunclassified
“…Os índices obtidos a partir desta análise contemplam R rs e X rs em várias frequências, permitindo avaliação de índices associados à resistência total, não homogeneidade e complacência dinâmica do sistema respiratório. (1)(2)(3)(4)6,8,(9)(10)(11)(12)14,16,18)…”
Section: Impedância Pulmonarunclassified
“…We found that the differences shown by spirometry in older age groups were not present in resistance and reactance values measured by IOS. IOS measures airway impedance, which is a function of resistance and reactance, thus predicts about the peripheral airway obstruction and detects inspiratory and expiratory changes in airway resistance in asthmatic children 7,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies focused on within‐breath versus whole breath analysis of IOS signals. Sol et al 8 hypothesized that analysis of inspiratory and expiratory IOS measurements would be more sensitive than whole‐breath analysis in differentiating lung function in children with asthma compared with those without asthma. Whole‐breath R5 and AX were significantly higher in asthmatic children compared with normal controls, while X5 was significantly lower.…”
Section: Forced Oscillatory Based Studiesmentioning
confidence: 99%